1993
DOI: 10.1017/s003329170002643x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and social correlates of the onset of affective disorders among pregnant women

Abstract: SynopsisOne hundred and twenty women recruited from attenders at the antenatal clinic of the Obstetrics Department of a general hospital were asked to complete ad hoc questionnaires during pregnancy; they were then interviewed by psychiatrists using a structured diagnostic interview, the Schedule for Affective Disorders and Schizophrenia (SADS). Nineteen (16%) women were identified as having an onset of an affective disorder during the period of pregnancy, mainly (68%) during the first trimester. As compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 47 publications
6
68
0
3
Order By: Relevance
“…The only studies on depression in the early to middle stage of pregnancy in Japan are those by Kitamura et al [5,10] and Sugawara et al [6], and our findings this time basically support their results.…”
Section: Depressionsupporting
confidence: 90%
See 4 more Smart Citations
“…The only studies on depression in the early to middle stage of pregnancy in Japan are those by Kitamura et al [5,10] and Sugawara et al [6], and our findings this time basically support their results.…”
Section: Depressionsupporting
confidence: 90%
“…Furthermore, they [5,10] cite 'first pregnancy or the first delivery with a history of previous termination of pregnancy' as risk factors for depression. We included the number of children and history of miscarriage in our current study, but found no association between these factors and depression.…”
Section: Depressionmentioning
confidence: 99%
See 3 more Smart Citations